Construction of Islamic Character Education in Deli Malay Culture in Medan City - Hidayat, Rahmat; Hasballah, Zamakhsyari; Alfiansyah Siregar, Fandi (Universitas Dharmawangsa Medan, 2020)
Malay Deli is one of the Malay sub-groups who live in Medan City. This tribe has awealth of cultural values which are used as a basis for the formation of the characterof its people. Malay Deli is one of the tribes that combines tradition and teachings fromIslam, this is in accordance with the philosophy in their lives